The role of inflammation in neurological disorders: a brief overview of multiple sclerosis, Alzheimer’s, and Parkinson’s disease’ - Cantero-Fortiz, Yahveth; Boada, Mercè (Frontiers in Neurology, 2024)
Neuroinflammation is a central feature in the pathophysiology of several neurodegenerative diseases, including MS, AD, and PD. This review aims to synthesize current research on the role of inflammation in these conditions, emphasizing the potential of inflammatory biomarkers for diagnosis and treatment. We highlight recent findings on the mechanisms of neuroinflammation, the utility of biomarkers in disease differentiation, and the implications for therapeutic strategies. Advances in understanding inflammatory pathways offer promising avenues for developing targeted interventions to improve patient outcomes. Future research should focus on validating these biomarkers in larger cohorts and integrating them into clinical practice to enhance diagnostic accuracy and therapeutic efficacy.